2022
DOI: 10.5534/wjmh.200176
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum 25-Hydroxyvitamin D Level as a Potential Risk Factor of Erectile Dysfunction in Elderly Men with Moderate to Severe Lower Urinary Tract Symptoms

Abstract: Purpose To evaluate the correlation between vitamin D level and erectile dysfunction (ED) in male lower urinary tract symptoms (LUTS) patients. Materials and Methods We analyzed data from 534 male patients who were tested for LUTS from 2014 to 2017. LUTS severity was classified into mild (≤7) or moderate to severe (≥8) based on total IPSS scores. Vitamin D deficiency was defined as a serum 25-hydroxyvitamin D [25(OH)D] level of less than 20 ng/mL. The severity of ED was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Many studies have shown a strong link between 25(OH)D and ED (Crafa et al, 2020;Horsanalı et al, 2020). Other studies have reported that 25(OH)D is also significantly lower in ED patients with diabetes and ED patients with lower urinary tract symptoms (Kim & Cho, 2022;Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Many studies have shown a strong link between 25(OH)D and ED (Crafa et al, 2020;Horsanalı et al, 2020). Other studies have reported that 25(OH)D is also significantly lower in ED patients with diabetes and ED patients with lower urinary tract symptoms (Kim & Cho, 2022;Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 85%
“…Many studies have shown a strong link between 25(OH)D and ED (Crafa et al, 2020; Horsanalı et al, 2020). Other studies have reported that 25(OH)D is also significantly lower in ED patients with diabetes and ED patients with lower urinary tract symptoms (Kim & Cho, 2022; Liu et al, 2022). Another study showed that serum L‐carnitine and 25(OH)D's were significantly reduced in ED patients who did not respond to oral sildenafil citrate (Mostafa et al, 2019).…”
Section: Introductionmentioning
confidence: 89%
“…The age dependence of hypovitaminosis D and ED seems to suggest a possible relationship between the two conditions. Consistent with this theory, it was observed that in patients older than 60 years with moderate to severe ED and lower urinary tract symptoms (LUTS), 25(OH)D levels and VDD were the independent risk factors for ED in the multivariate regression analysis, whereas these associations were not observed in analyses performed in other subgroups according to age and LUTS severity [ 14 ].…”
Section: Introductionmentioning
confidence: 92%
“…Add a data sharing statement to the paper Add the data sharing statement to the final proof of the edited paper (Fig. 5) [4].…”
Section: How To Deposit Data To the Harvard Dataverse Repositorymentioning
confidence: 99%